2014
DOI: 10.1007/978-1-4939-2214-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of G4 Quadruplex Telomerase RNA Unwinding by the RNA Helicase RHAU

Abstract: G4 quadruplexes are stable secondary structures prevalent in DNA and RNA that exhibit diverse regulatory functions. Herein, we describe an in vitro technique using the purified RNA helicase RHAU to unwind a G4 quadruplex identified near the 5' end of the human telomerase RNA (hTR). A synthetic RNA corresponding to the quadruplex forming region of hTR (hTR10-43), as well as a predicted complementary strand (25P1), are combined in a reaction containing the purified helicase and ATP. Reaction products and appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…RHAU 53-105 and full length RHAU were expressed and purified as described previously [ 31 , 43 ]. After removal of the hexahistidine affinity tag by thrombin digestion, the protein was further purified by size exclusion chromatography on a HiLoad Superdex 75 26/60 (ÄKTA GE Healthcare, Mississauga, Canada) in 10 mM HEPES (pH 7.5), 150 mM NaCl (5 mL load volume).…”
Section: Methodsmentioning
confidence: 99%
“…RHAU 53-105 and full length RHAU were expressed and purified as described previously [ 31 , 43 ]. After removal of the hexahistidine affinity tag by thrombin digestion, the protein was further purified by size exclusion chromatography on a HiLoad Superdex 75 26/60 (ÄKTA GE Healthcare, Mississauga, Canada) in 10 mM HEPES (pH 7.5), 150 mM NaCl (5 mL load volume).…”
Section: Methodsmentioning
confidence: 99%
“…Another study confirmed that the interaction between DHX36 and the TERC G-quadruplex disrupts the formation of P1 helix, a structure which defines template boundary for reverse transcription. DHX36 was sufficient to unwind the quadruplexes and promote the formation of a stable P1 helix, and DHX36 depletion led to a reduction in average telomere length 138,141 . Besides the function on telomere maintenance, DHX36 regulates translation, although the precise mechanism has not yet been elucidated.…”
Section: Rhau (Dhx36)mentioning
confidence: 99%
“…All standard laboratory chemicals and reagents were purchased from Thermo Fisher Scientific. The recombinant full-length RHAU protein, RHAU E335A mutant, RHAU iso.2 , RHAU ⌬RSM , RHAU (1-614), RHAU(1-760), and RHAU(53-105) truncations were cloned using standard molecular biology techniques and expressed and purified as described previously (23,41).…”
Section: Methodsmentioning
confidence: 99%